Comparative analysis of simplified and standard fuzzy logic controller in vector controller PMSM - Siti Noormiza , Mat Isa; Zulkifilie, Ibrahim; Jurifa , Mat Lazi (2011)
This paper presents a comparative analysis of simplified fuzzy logic controller (FLC) for speed performance in vector-controlled permanent magnet synchronous motor (PMSM) drive. The control strategy focuses on fuzzy rule basewhich are contribute to some level of output in obtaining the desired performance. The objective of this research is minimizing the number of rule base used by the PMSM drive besides erform desired output. Two FLCs with reduced rule base (9- rules and 7-rules) are designed and the performance results are compared and ernluated with the standard FLC (49-rules). The simplification of rule base is determined by eliminating some of rule bases that are infrequently fired by the PMSM drive. The standard FLC consists of 49-rules which are determined based on common criteria from many literatures. Two simplified FLCs consist of 9-rules and 7-rules are obtained by knowledge and experience. The simulation results show both simplified FLCs obtain nearly equivalent performance with the standard FLC. The performance of all FLCs over load disturbance and parameter variations are compared an